A comparative study of the poetics of Plato and Qur'an - Zekavat, Massih (Primerjalna književnost, 2015)
This article aims to comparatively investigate the poetics of Plato and Qur'an and explicate the reasons behind their ambivalent denunciations of poets and poetry in an attempt to open a ground for the meeting of their descendent literary traditions, and to suggest that literature and poetry can proffer worldly outlooks to transcend mundane boundaries.
Keywords: antična filozofija; književnost; Koran; navdih; Plato; poezija; primerjalna poetika; primerjalne študije; resnica